Design and fabrication of stationery rack - Ahmad Hazury, Hamid (2007)
Development of this stationery rack is for stationeries such as pen, pencil and ruler on the table. With more stationeries case, this rack can store numbers of stationeries and easy to find. This stationery rack is made from mild steel sheet metal. It has rotating boxes which is use as place to store stationeries. This rack will help to store stationeries in place and easy to take stationeries from it. Whole of this project is particular involves the stationery rack. Diploma final year project will allocate one semester to complete the project. This project also required the adequate student to finish a task given. The tasks division need to apply, for the entirely two part will be make that is a process to development of parts and assemble the stationery rack.